Exploring the Potential of Natural Media in Pancasila Education to Foster an Environmentally Conscious Attitude in Elementary School Students - Nanda Amalia; Oki Suprianto; Firman Robiansyah (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This study aims to explore the use of natural media in Pancasila Education to foster environmental awareness among elementary school students. This study uses a qualitative approach with an exploratory type. The study was conducted at SD Peradaban Serang in January 2026 with research subjects consisting of two Pancasila Education teachers and ten fourth and fifth grade students selected using purposive sampling. Data collection was conducted through observation, semi-structured interviews, and documentation. Data analysis used the interactive model of Miles and Huberman, which included data reduction, data presentation, and conclusion drawing. Data validity was ensured through method triangulation. The research findings indicate that natural media, such as dried leaves, small stones, twigs, and plants in the school environment, can be utilized as contextual learning resources in Pancasila Education. The use of natural media was able to increase students’ activeness, enthusiasm, and engagement in the learning process. In addition, nature-based learning encouraged the development of environmental awareness, responsibility, and cooperation as forms of practicing Pancasila values, particularly the second, third, and fifth principles. Teachers played an important role in planning, implementing, and connecting the use of natural media with learning materials and Pancasila values, thereby making the learning process more meaningful. The conclusion of this study shows that natural media is an effective alternative learning resource in supporting contextual Pancasila education and contributes to fostering environmental awareness among elementary school student.